GDM 4: High yielding, high oil content and bold seeded variety of Indian mustard [Brassica juncea (L). Czern and Coss]: GDM 4: HIGH YIELDING, HIGH OIL CONTENT AND BOLD SEEDED VARIETY OF INDIAN MUSTARD - K P PRAJAPATI; P J PATEL; J R PATEL; A L JAT; G P GANGWAR; B K PATEL; A G DESAI (Journal of Oilseeds Research, 2017)
Extensive crop breeding efforts were made to develop high yielding, high oil content and bold seeded varieties for mustard growing area of Gujarat. As a result, the genotype SKM 301 (GDM 4) was identified and evaluated for its yield potentiality along with state and national check varieties (Varuna, GM 3 and Kranti) at various locations of Gujarat as state trial and different locations of Zone IV under AICRP on Rapeseed-Mustard trials. As compared to check varieties, the entry SKM 301 recorded higher mean seed yield 2417 kg/ha and high oil content (39.02%) and 1000-seed weight (5.70 g). Tolerant to lodging and shattering are additional features of this entry, SKM 301.